Nutritional Approaches In The Prevention And Management Of Hepatocellular Carcinoma: A Review - B, Devasena,; Javed, Tahseen; W, Anitha,; N B, Geetha; Mahalakshmi, Mahalakshmi (Journal of Neonatal Surgery, 2025)
Hepatocellular carcinoma (HCC) is one of the leading causes of cancer-related mortality globally. Emerging evidence indicates that dietary interventions can play a significant role in both the prevention and management of HCC, particularly among high-risk populations. This review explores the impact of nutritional factors on HCC progression, focusing on the protective roles of antioxidants, polyphenols, and specific functional foods. High intake of fruits, vegetables, omega-3 fatty acids, and plant-derived compounds has been associated with anti-carcinogenic effects, while excessive consumption of red meat, sugar, and saturated fats may elevate HCC risk. Furthermore, selected juices, herbal extracts, and bioactive food combinations exhibit hepatoprotective and anti-tumor properties in both in vitro and in vivo studies. This comprehensive review underscores the potential of evidence-based dietary strategies in reducing liver cancer burden and improving the prognosis of HCC patients.